2009
DOI: 10.1007/s00542-008-0769-y
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic actuator design for single-axis micro-gyroscopes

Abstract: An innovative magnetically levitated system design is presented in this paper. The proof mass, used as the seismic detection components for gyroscopes, is levitated by the presented micro-coil actuator so that the concerns that mechanical fatigue, asymmetry and misalignments, which are inevitably present in the traditional mechanical springs design, can be ruled out. In addition, the limited range of dual-axis motion of the proof mass is completely relaxed and therefore the resolution and sensitivity of the gy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…(Chen et al 2005;Duan et al 2008;Tsai et al 2009;Zhang 2006;Xu et al 2009;Kagawa et al 2006;Xie and Fedder 2003). Adoption of micro electro mechanical systems (MEMS) technology for fabricating gyroscopes has allowed the fabrication of smaller, cheaper and much more energy efficient devices than conventional macro-sized devices (Kulygin et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…(Chen et al 2005;Duan et al 2008;Tsai et al 2009;Zhang 2006;Xu et al 2009;Kagawa et al 2006;Xie and Fedder 2003). Adoption of micro electro mechanical systems (MEMS) technology for fabricating gyroscopes has allowed the fabrication of smaller, cheaper and much more energy efficient devices than conventional macro-sized devices (Kulygin et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, Tsai et al inductively levitated a conducting cap-shaped rotor, and electrostatically revolved it with a speed of 2000 r.p.m. [52]. Subsequently, Kraft's group proposed a design of the accelerator and experimentally demonstrated that a 1×1 mm 2 sized and 7 µm thick micro object could be levitated to a maximum height of 82 µm and propelled forward continuously at a maximum average forward velocity of 3.6 mm s −1 [126].…”
Section: Hybrid Levitation Micro-actuatorsmentioning
confidence: 99%
“…The main disadvantage of the above ILMA prototypes was a very high operating temperature, rising up to 600 • C [50] due to the planar design of the micro-coils. Proposing a spiral coil design as shown in Figure 4b, Tsai et al fabricated a prototype that was able to stably levitate a conducting cap-shaped proof mass with an operating temperature of 100 • C [52].…”
Section: Inductive Levitation Micro-actuatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Except for electrostatic and piezoelectric methods, rather few alternatives have been investigated and tested; examples of typical solutions presented in literature include designs based on thermal (Shakoor et al, 2009) and magnetic (Paoletti et al, 1996;Tsai et al, 2009) actuation, or optical sensing (Bochobza-Degani et al, 2000;Norgia & Donati, 2001). …”
Section: Actuation and Sensing Mechanismsmentioning
confidence: 99%